2003
DOI: 10.1161/01.cir.0000058200.90059.b1
|View full text |Cite
|
Sign up to set email alerts
|

AT 1 Receptor Agonistic Antibodies From Preeclamptic Patients Stimulate NADPH Oxidase

Abstract: Background-We recently identified agonistic autoantibodies directed against the angiotensin AT1 receptor (AT 1 -AA) in the plasma of preeclamptic women. To elucidate their role further, we studied the effects of AT 1 -AA on reactive oxygen species (ROS), NADPH oxidase expression, and nuclear factor-B (NF-B) activation. Methods and Results-We investigated human vascular smooth muscle cells (VSMC) and trophoblasts, as well as placentas. AT 1 -AA were isolated from sera of preeclamptic women. Angiotensin II (Ang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
200
1
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(215 citation statements)
references
References 33 publications
(27 reference statements)
9
200
1
5
Order By: Relevance
“…Indeed, AT-1AA functioned in a Western blot at least as well as currently available commercial antibodies to the AT-1 receptor. Dechend et al (68,69) confirmed these findings by relying on co-immunoprecipitation studies. They could not find evidence for calcium signaling or smooth muscle cell contraction resulting from the autoantibodies.…”
Section: Circulating Autoantibodiesmentioning
confidence: 85%
“…Indeed, AT-1AA functioned in a Western blot at least as well as currently available commercial antibodies to the AT-1 receptor. Dechend et al (68,69) confirmed these findings by relying on co-immunoprecipitation studies. They could not find evidence for calcium signaling or smooth muscle cell contraction resulting from the autoantibodies.…”
Section: Circulating Autoantibodiesmentioning
confidence: 85%
“…AT1 is constitutively expressed in placental VSMCs as shown in the Western blot data. AT1 plays important roles in angiogenic, inflammatory and oxidative stress responses in the placental vasculature [30][31][32][33]. A recent study by Herse et al showed that AT1 receptor mRNA expression was 10-fold higher in the placenta than in the decidua tissues in both normal and preeclamptic pregnancies, but no difference was noticed for AT1 mRNA expression between normal and preeclamptic placental tissues [34].…”
Section: Discussionmentioning
confidence: 99%
“…According to present data, AT 1 -AAs were suggested to have similar effects. Dechend et al reported that AT 1 -AAs induced signaling in vascular cells including AP-1 and NF-κB activation (10,11). Both of these nuclear factors participate in inflammation (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…AT 1 -AAs induced signaling in vascular cells and trophoblasts including activator protein-1 (AP-1) and nuclear factorkappa B (NF-κB) (10,11), and activated calcineurin-NFAT (nuclear factor of activated T cells) through increased intracellular Ca 2+ mobilization in Chinese hamster ovary cells transferred with the rat AT 1A receptor (12). However, there were limited data related to the role of AT 1 -AAs in pathogenesis of hypertension.…”
Section: Introductionmentioning
confidence: 99%